1988
DOI: 10.1007/bf01655437
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency and hyperparathyroidism with severe bone disease

Abstract: Circulating 25‐hydroxycholecalciferol (25OHD3) levels are low in Saudi Arabia due to a lack of sunlight exposure and a low dietary intake of vitamin D (vit D). Recent studies in animals and man indicate that the half‐life of 25OHD3 is reduced in states of hyperparathyroidism. We, therefore, reviewed the charts of 43 patients with primary hyperparathyroidism (HPT) to establish whether there was coexisting vit D deficiency and osteomalacia. In the 22 patients studied, 25OHD3 levels were below normal in 14 and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…Other Asian countries similarly reported that this condition remained uncommon with most patients presenting with severe osteitis fibrosa cystica. [6][7][8] In fact, the clinical and pathologic characteristics of patients with primary HPT recently reported from these developing countries mirror those reported in the West a few decades earlier. 8,9 A geographic or causative difference of this condition between different population groups has been proposed.…”
supporting
confidence: 58%
“…Other Asian countries similarly reported that this condition remained uncommon with most patients presenting with severe osteitis fibrosa cystica. [6][7][8] In fact, the clinical and pathologic characteristics of patients with primary HPT recently reported from these developing countries mirror those reported in the West a few decades earlier. 8,9 A geographic or causative difference of this condition between different population groups has been proposed.…”
supporting
confidence: 58%
“…Exact pathogenesis of this younger age of presentation has not been established. Suboptimal vitamin D nutrition is linked with parathyroid adenoma growth [33] and vitamin D deficiency in this part of the world may be a causative factor. In the current decade, patients presenting with metabolic complications, e.g., hypercalcemic crisis, palpable neck mass and pathological fractures have decreased significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Similar clinical and pathological features of this disease have been reported from other developing countries. 22 24 …”
Section: Discussionmentioning
confidence: 99%